2020
DOI: 10.3390/en13112791
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments and Future Challenges in Designing Rechargeable Potassium-Sulfur and Potassium-Selenium Batteries

Abstract: The use of chalcogenide elements, such as sulfur (S) and selenium (Se), as cathode materials in rechargeable lithium (Li) and sodium (Na) batteries has been extensively investigated. Similar to Li and Na systems, rechargeable potassium–sulfur (K–S) and potassium–selenium (K–Se) batteries have recently attracted substantial interest because of the abundance of K and low associated costs. However, K–S and K–Se battery technologies are in their infancy because K possesses overactive chemical properties compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Compared with Li/Na-S batteries, research on K-S batteries has emerged because of the low redox potential and abundant reserves of K. [149] However, K is much more reactive than its Li and Na counterparts, and the larger ionic size of K + also results in sluggish reaction kinetics, hindering the practical applications of K-S batteries. To resolve these obstacles, both sulfur cathodes and electrolytes require rational design.…”
Section: K-s Batteriesmentioning
confidence: 99%
“…Compared with Li/Na-S batteries, research on K-S batteries has emerged because of the low redox potential and abundant reserves of K. [149] However, K is much more reactive than its Li and Na counterparts, and the larger ionic size of K + also results in sluggish reaction kinetics, hindering the practical applications of K-S batteries. To resolve these obstacles, both sulfur cathodes and electrolytes require rational design.…”
Section: K-s Batteriesmentioning
confidence: 99%
“…[ 17 ] However, the large ionic radius of potassium ions imposes great limitations on their diffusion and intercalation in electrodes, leading to poor electrochemical performance of KIBs so far. [ 18 ] Commercial graphite is capable of storing potassium ions but shows low reversible specific capacity (279 mA h g −1 ) and sluggish reaction kinetics. [ 19 ] In order to tackle this problematic issue, considerable efforts have to be devoted to design of high‐capacity anode materials.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Se as cathode material still has many problems in the KÀ Se batteries system: (1) the large size of selenium limits the reaction of selenium with potassium; (2) the production of soluble intermediate polyselenides may lead to the shuttle effect, which rapidly decays the capacity; (3) appropriate electrolyte and electrode structure are supposed to be explored to improve material properties. [12,13] At present, researchers have used many methods to buffer the volume expansion and inhibit the shuttle effect of Se. For example, Sun's group reported that concentrated electrolyte could mitigate the dissolution and shuttle effect of potassium polysulfide in KÀ S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…investigated electrochemical performance and reaction mechanism for K−Se and K−Te batteries, and identified the reaction pathways of K−Se batteries based on a carbon/Se composite cathode and a highly concentrated ether based electrolyte as reversible stepwise phase transformation from solid‐state Se to soluble K 2 Se 5 , and to solid‐state K 2 Se 3 , K 2 Se 2 , and K 2 Se [10,11] . Se as cathode material still has many problems in the K−Se batteries system: (1) the large size of selenium limits the reaction of selenium with potassium; (2) the production of soluble intermediate polyselenides may lead to the shuttle effect, which rapidly decays the capacity; (3) appropriate electrolyte and electrode structure are supposed to be explored to improve material properties [12,13] …”
Section: Introductionmentioning
confidence: 99%